Self-distribution-function procedure in elastic incoherent neutron scattering for biosystems molecular motion characterization. Issue 3 (2010) - Magazù Magazù, Salvatore Salvatore; Migliardo Migliardo, Federica Federica; Benedetto Benedetto, Antonio Antonio; Gonzalez Gonzalez, Miguel Miguel; Mondelli Mondelli, Claudia Claudia
Abstract : In the present contribution we present a new procedure for the Mean Square Displacement (MSD) determination from Elastic Incoherent Neutron Scattering (EINS) where the connection between the Self-Distribution Function (SDF) and the measured EINS intensity profile is highlighted. We show how the SDF procedure allows both the total and the partial MSD evaluation, through the total and the partial SDFs. The procedure is applied on EINS data collected, by the IN13 backscattering spectrometer (ILL, Grenoble), on aqueous mixtures of sucrose and trehalose.